On travel as a desire for discoincidence. - Coelho, J. V. (Plataforma Barómetro Social, 2019)
Travel involves mobility, the confrontation of routine, and the normality of existing relationships. The 'discrepancy of oneself with oneself' is possible in this respect and implies the existence of what Giddens calls the 'reflexive project of the self,' a work of composition closely associated with the search for maintenance within a framework of fluid belonging, characterized by trust, a sense of stability, and ontological security. In Portugal, this is a social phenomenon that has garnered increasing attention in the media, political, and academic spheres, with particular emphasis on considering, in different contexts, the observable implications in terms of individuals' and groups' access (to mobility, movement, travel), ecological and socio-economic sustainability, the modification of living conditions, and horizons of personal cognition and reflexivity.